Effect of track curvature on the microstructure evolution and cracking in the longitudinal section of lower gauge corner flow lips formed in rails. (May 2022) - Mojumder, Soumyajit; Mishra, Kushal; Singh, Kritika; Qiu, Cong; Mutton, Peter; Singh, Aparna
Highlights: Flow lips were formed in rails extracted from mild curvature tracks. WEL and BEL were observed as the outermost layers in the flow lip regions. Multiple cracks with different propagation angles were found. Reverse transverse fracture might originate in cracks developed in the flow lips. The propensity for rail fracture increases with a decrease in track curvature. Abstract: The microstructure of the flow lips formed at the lower corner of gauge face in the longitudinal section of worn high rails serving in curved tracks has been investigated. The radii of the curved tracks are 1500 m (S1, sharper curve) and 4000 m (S2, milder curve). Sharper curves result in a higher angle of attack (AOA) between rail-wheel thus leading to higher lateral contact forces as well as tangential frictional forces thus facilitating plastic flow. Such conditions favour formation of flow lips where rail material flows from the rail upper gauge face to the lower corner of the gauge face. A combination of optical microscopy (OM), scanning electron microscopy (SEM), electron backscattered diffraction (EBSD) and nano-indentation hardness measurements have been used for the characterization of the flow lip. It is observed that the outermost region of the flow lip consists of a uniformly present white etching layer (WEL) followed by an intermittently present brown etching layer (BEL) where the WEL and BEL thickness is less for milder curves. The WEL has the highest hardness and consists of fine grains of ferrite and particles/fine fragments of cementite. The BEL is relatively softer than WEL and has a similar appearance to WEL, but patches of lamellar structure appear with increasing depth from the outer edge. Beyond the BEL region, layers of deformed pearlitic structure are observed, and a more intact pearlitic structure is observed at a much lower depth for the milder curve than the sharper curve. For both the curvatures at a given depth, the hardness of pearlite bears a Hall-Petch type of relationship to the pearlitic interlamellar spacing. However, the alignment of the deformed microstructure is heavily dependent on the curvature. It has been found to align almost parallel (4°–10°) to the rail longitudinal axis for the milder curvature and at around 21°–35° for the sharper curvature. Cracks originate from the brittle WEL region due to contact fatigue whereas crack propagation is driven by bending stresses. Cracks have been found to move parallel to the alignment of the deformed pearlite along longitudinal direction for the milder curvature. Alignment of pearlite also motivates the crack propagation trajectory for the sharper curvature and hence the crack moves at an angle between 21° and 35° with the longitudinal direction but becomes almost perpendicular after a distance. Shallow cracks travelling parallel to the rail outer edge in S2 can result in spalling of the rail material leading to wear, whereas for sharper curves, cracks run deeper into the railhead. Thus, the tendency for rail failure through 'Reverse Transverse Fracture' – which involves crack initiation at the lower gauge corner and propagation into the railhead – increases with the sharpness of the rail curvature.